2013
DOI: 10.1126/scitranslmed.3006034
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Titin-Derived HLA-A1–Presented Peptide as a Cross-Reactive Target for Engineered MAGE A3–Directed T Cells

Abstract: MAGE A3, which belongs to the family of cancer-testis antigens, is an attractive target for adoptive therapy given its reactivation in various tumors and limited expression in normal tissues. We developed an affinity-enhanced T cell receptor (TCR) directed to a human leukocyte antigen (HLA)–A*01–restricted MAGE A3 antigen (EVDPIGHLY) for use in adoptive therapy. Extensive preclinical investigations revealed no off-target antigen recognition concerns; nonetheless, administration to patients of T cells expressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
581
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 582 publications
(585 citation statements)
references
References 46 publications
3
581
0
1
Order By: Relevance
“…24 MAGE-A3 a3a TCR T cells were subsequently transduced with CXCR2, and sorted by combined tetramer and antibody staining into a MAGE-A3 a3a TCR + CXCR2_GFP pos or MAGE-A3 a3a TCR + CXCR2_GFP neg fraction (from here designated “CXCR2” and “Mock”) (suppl. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 MAGE-A3 a3a TCR T cells were subsequently transduced with CXCR2, and sorted by combined tetramer and antibody staining into a MAGE-A3 a3a TCR + CXCR2_GFP pos or MAGE-A3 a3a TCR + CXCR2_GFP neg fraction (from here designated “CXCR2” and “Mock”) (suppl. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lentiviral vector containing high affinity MAGE-A3 a3a TCR 24 and corresponding packaging and envelope plasmids (VSVG, REV and gag/pol) was generously provided under MTA.…”
Section: Methodsmentioning
confidence: 99%
“…In vivo replication of the interaction between MAGE-A3 TRCR-transduced T-cells and cardiomyocytes replicated these findings. (Cameron et al 2013) This unexpected off-target toxicity highlights the importance of confirming the specificity of engineered TCRs to the best of our capabilities prior to clinical investigation.…”
Section: Genetic Transfer Of Exogenous Tcrsmentioning
confidence: 99%
“…Further investigation revealed that the affinity enhancement of the TCR resulted in recognition of a similar peptide expressed in cardiac muscle, leading to acute cardiac rejection. 33 Following these unexpected deaths, an extensive investigation was undertaken, with initial experiments demonstrating no cross-reactivity with standard myocyte cell culture models. Only the use of highly purified human cardiomyocytes derived from induced pluripotent stem cells revealed the reactivity with the titin peptide expressed in beating cardiac myocytes.…”
Section: Off-target Toxicitiesmentioning
confidence: 99%